Effect of BA and NAA on in Vitro Culture of Young Leaves of Caladium bicolor Vent - รัตนา ดร.ขวัญเดือน; แสงจันทร์จิรเดช ศุภาวีร์; มุ่งลือ ดร.พักพล (Journal of Food Health and Bioenvironmental Science, 2017)
Effects of N6-Benzyladenine (BA) and α-Naphthalene acetic acid (NAA) on in vitro culture of Caladium bicolor Vent. young leaves were investigated. Young leaf explants (0.5 x 0.5 cm.) were cultured on MS (Murashige and Skoog, 1962) medium supplemented with combinations of BA at the levels of 0, 1, 2, 3, 4, 5 mg.L-1 with 0 or 0.5 mg.L-1 NAA, and cultured for 8 weeks. The results showed that the highest callus induction (50%) and developing shoots were also found in MS medium incorporated with 1 mg.L-1 BA and 0.5 mg.L-1 NAA. Subsequently, callus and shoots were then transferred to MS medium supplemented with BA at the concentrations of 0, 1, 2, 3, 4 and 5 mg.L-1 and 0 and 0.5 mg.L-1 NAA, and cultured for 8 weeks in order to induce shoot multiplication. The results showed that the medium containing 3 mg.L-1 BA combined with 0.5 mg/l NAA was the best shoot multiplication medium and gave the highest percentage of shoot multiplication from the callus (50%). After sub culturing young shoots on different media, shoot multiplication was found in all media types. However, MS medium containing 1 mg.L-1 BA produced the best shoot multiplication (4 shoots per explants), whereas MS medium containing 4 mg.L-1 BA and 0.5 mg.L-1 NAA provided the longest shoot length (5.3 cm./shoot). All healthy regenerated shoots and roots were then transplanted to the greenhouse and observed for 5 month. We found that the highest survival rate of plantlets observed was 90% and occurred when the plantlets were planted on plastic pots containing dried clay powder, dried grass and rice-husk ash at the ratio of 2 : 1 : 1.